Fluoride release of giomer and resin based fissure sealants = Liberación de flúor de sellantes de fosas y fisuras a base de resina y/o ionómero - Şişmanoğlu, Soner
Fissure sealants are applied to teeth to prevent caries development. The presence of the fissure sealant creates a protective barrier, which prevents plaque accumulation to the pits and fissure. They have a significant role in preventing pit and fissure caries. The aim of this study was to evaluate the time-dependent fluoride ion release of giomer- and resin-based fissure sealants. Fissure sealants were divided into 4 groups: BeautiSealant (Shofu, Japan), Clinpro Sealant (3M ESPE, USA), Helioseal F (Ivoclar Vivadent, Liechtenstein), Fissurit F (Voco, Germany). Disk shaped samples were prepared for each sealant material tested, and they were transferred into polyethylene vials containing 5 ml of deionized water. Fluoride ion diffusion was determined on days 1,2,3,7,14,21, and 28 (n=7). The fluoride concentration in these samples was analyzed using a pre-calibrated spectrophotometer in parts per million (ppm). These experiments were performed in triplicates at room temperature. ANOVA and Tukey's HSD test were used for statistical analysis. BeautiSealant was released the highest amount of fluoride on day 1 (5.33 ppm), followed by a sudden decrease on the day 2 (2.17ppm). The burst effect was observed only in this group. Clinpro Sealant, Fissurit F and HelioSeal F groups presented fluoride release of 2.69, 2.94 and 2.91 ppm on the first day, respectively, without a significant difference (p>0.05). After the first week, a constant fluoride release level has been reached. The fluoride release for the three resin-based fissure sealants was slightly lower than that for the giomer-based. After the first week, materials exhibited no significant difference and reached a plateau. The usage of a high and prolonged fluoride-releasing fissure sealant material should be considered by clinicians, particularly in patients with caries risk.